Cardiac Conduction System Anomalies and Sudden Cardiac Death: Insights from Murine Models - Aranega, Amelia E.; de la Rosa, Angel J.; Franco, Diego (Frontiers in Physiology, 2012)
The cardiac conduction system (CCS) is a series of specialized tissues in the heart responsible for the initiation and co-ordination of the heartbeat. Alterations in the CCS, especially the His-Purkinje system, have been identified as an important player in the generation of lethal arrhythmias. Unstable arrhythmias secondary to channelopathies highly increase the risk of sudden cardiac death (SCD). Sudden cardiac death is a major contributor to mortality in industrialized nations, and most cases of SCD in the young are related to inherited ion channel diseases. In this review we examine how murine transgenic models have contributed to understanding that a broad variety of cardiac arrhythmias involve the cardiac specialized conduction system and may lead to sudden cardiac death.